Kesan Intervensi Kaunseling Kognitif Tingkah Laku Terhadap Penyesuaian Psikologi Wanita Pasca Perceraian - Paslan, Nur Azmina (2021)
This study aims to examine the effects of Cognitive Behavioral Therapy interventions on women‘s post-divorce adaptation. The study also examines the differences in the effects of Cognitive Behavioral Therapy approach interventions on (i) love relationships, (ii) anger, (iii) sadness, (iv) self-esteem, (v) social self-esteem, and (vi) social trust between post-divorce women as well as to identify psychological and non-psychological factors on post-divorce women's psychological adaptation.